Pengaruh Pola Asuh Orang Tua terhadap Perkembangan Sosial Anak Usia Dini di PAUD - Sri Putri Enjelita; Nurul Aini Mm. Sodik; Nabila Nggai; Fitriyawati Ladiku (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study aims to determine the influence of parenting styles on the social development of early childhood at the Al-Fajril Ulum Preschool and Kindergarten (PAUD TPA Al-Fajril Ulum). Observations were conducted to analyze how four types of parenting styles democratic, authoritarian, permissive, and neglectful influence children's social skills in the context of interaction, communication, decision-making, and the ability to establish relationships with peers. The study used a quantitative method with an ex post facto design, involving a sample of 8 children. Data collection instruments included questionnaires and observation sheets for children's social development based on indicators for each parenting style. The results showed that democratic parenting had the most significant positive influence on children's social development, marked by an increase in children's ability to express opinions, cooperate, respect others, and demonstrate social independence. Conversely, authoritarian and neglectful parenting styles had negative influences due to low emotional warmth, lack of dialogue, and minimal stimulation received by children. Permissive parenting showed a positive influence but not as strong as democratic parenting due to weak parental boundaries and control. Overall, the research findings confirm that the quality of parenting styles plays a direct role in shaping the social behavior of early childhood.